Simple linearising front‐end‐circuit for giant magneto‐resistance sensors. Issue 2 (1st January 2018) - Sen, T.; Anoop, C.S.; Sen, S.
Abstract : A simple and efficient linearisation front‐end circuit for giant magneto‐resistance (GMR) sensors are presented. This circuit essentially uses only a single opamp to linearise the (non‐linear) GMR sensor output. A novel methodology that places an active GMR element, present inside the GMR sensor, in the feedback loop of the opamp is employed for linearisation. Initial validation of the front‐end is performed using simulation and emulation studies. Then, the front‐end, fabricated on a printed‐circuit board, is interfaced with a GMR sensor. Experimentation showed output non‐linearity is around 0.6%. The proposed front‐end possess merits, like, low component‐count and minimal error, no requirement of expensive amplifiers or matched resistors for linearisation, fast response, over the existing methods.